Measuring the indirect effects of some factors adopted within the multi-level theory on sustainable organizational performance through strategic thinking skills - Alaa Farhan Talib; Ahmed Kazem breas (Iraqi Journal for Administrative Sciences, 2025)
This research aims to explore the nature of the indirect influential relationship of some factors adopted within the multi-level theory and sustainable organizational performance through strategic thinking skills, based on the opinions and ideas of previous researchers in clarifying the multiple comprehensive view of the dimensions of each of the variables above. Regarding the first variable (multi-level theory), most researchers who were interested in studying this field agreed that any organizational phenomenon is structured in hierarchically overlapping units, and that failure to know this hierarchical arrangement leads to inaccurate research results. As for sustainable organizational performance, it has been adopted Classification (ElKington: 1997), which indicated that the dimensions of sustainable performance are the economic axis, the environmental axis, and the social axis), in addition to adopting the axis of building a culture of sustainable performance from the author (Turban, 2010). Finally, the researchers relied on the model (Wooton & Horne: 2010) with regard to thinking skills The strategic approach was based on three basic principles: the first seeks to know the nature of the relationship between the dimensions of the above variables, the second aims to explore the relative importance of the research variables, and the last attempts to identify the nature of the indirect influential relationships between the research variables From a doctoral thesis entitled (Reflection of dynamic capabilities and strategic thinking skills on sustainable organizational performance within the framework of multi-level theory).